FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN INFEKSI SALURAN PERNAFASAN AKUT PADA ANAK USIA BAWAH LIMA TAHUN - Elfida, Elfida; Azwari, Azwari; AS, Emilda (Jurnal Kesehatan Ibu dan Anak, 2014)
Acuta Respiratory Infection (ARI) is a major public health problem, this is still rising toddlers ARI deaths due to pneumonia in infants. To prevent death ARI proven effective way now is to complete immunization , prevention of ARI is to live a healthy , well nourished avoiding air pollution from either inside or outside the home , a good state of residence .Selain itu factors affecting the incidence oARI one of which is the mother's socio-economic and knowledge . The purpose of this study to determine Factors Affecting AcuteRespiratory Infections in Children Under Five Years of Age in the West Langsa Health Center in 2013,with a cross-sectional design and Analytical descriptive nature . The population is all that is in the health center toddlers Langsa Barta . The samples were taken with 96 respondents Acidental sampling techniques in health centers of West Langsa. From the research found no relationship between the state of ARI incidence place stay with the toddler with a value of P- 0.000 and no significant relationship between maternal knowledge with ARI incidence in infants with a P value = 0.00 . As well as the results found no significant association between socioeconomic ARI incidence in infants with a value of P - 0.098 . It is recommended to health workers to provide counseling either directly or indirectly, to increase knowledge about the mothers who have infants with respiratory disease association stateof residence .